Immune Regulation by Pericytes: Modulating Innate and Adaptive Immunity - Navarro, Rocío; Compte, Marta; Álvarez-Vallina, Luis; Sanz, Laura (Frontiers in Immunology, 2016)
Pericytes are mural cells that surround endothelial cells in small blood vessels. Pericytes have traditionally been credited with structural functions, being essential for vessel maturation and stabilization. However, an accumulating body of evidence suggests that pericytes also display immune properties. They can respond to a series of proinflammatory stimuli and are able to sense different types of danger due to their expression of functional pattern recognition receptors, contributing to the onset of innate immune responses. In this context, pericytes not only secrete a variety of chemokines, but they also overexpress adhesion molecules such as ICAM-1 and VCAM-1 involved in the control of immune cell trafficking across vessel walls. In addition to their role in innate immunity, pericytes are involved in adaptive immunity. It has been reported that interaction with pericytes anergizes T cells, which is attributed, at least in part, to the expression of PD-L1. As components of the tumor microenvironment, pericytes can also modulate the antitumor immune response. However, their role is complex and further studies will be required to better understand the crosstalk of pericytes with immune cells in order to consider them as potential therapeutic targets. In any case, pericytes will be looked at with new eyes by immunologists from now on.